Correlation between Urinary Neutrophil Gelatinase-Associated Lipocalin with Proteinuria and Glomerular Filtration Rate in Childhood Idiopathic Nephrotic Syndrome - Jalil, Farhana; Hanif, Mohammed (Journal of Armed Forces Medical College, Bangladesh, 2020)
Introduction:Neutrophil gelatinase-associated lipocalin (NGAL) is a small protein belonging to the lipocalin superfamily, which is rapidly upregulated in response to renal injury and has proven to be an emerging biomarker for acute kidney injury (AKI). Recently it has been found that NGAL can also predict chronic kidney disease progression. Steroid resistant nephrotic syndrome has been found to be one of the important cause of chronic kidney disease in children. Therefore this study was conducted to evaluate whether urinary NGAL can correlate with proteinuria or glomerular filtration rate (GFR) in idiopathic nephrotic syndrome in children. Objectives:To find out the correlation between urinary NGAL with proteinuria and GFR in childhood idiopathic nephrotic syndrome. Materials and Methods:This cross-sectional was conducted in the Department of Pediatric Nephrology, Dhaka Shishu Hospital and Department of Pediatric Nephrology, Bangabandhu Sheikh Mujib Medical University from June 2014 to May 2015. Fifty-one children with idiopathic nephrotic syndrome were enrolled for the study. Urinary NGAL was measured using a commercially available HUMAN NGAL/LIPOCALIN 2 ELISA kit.The estimated GFR (eGFR) was calculated using revised Schwartz formula as follows: eGFR (ml/min/1.73m2) = 0.413 x (height in centimeters/ serum creatinine in mg/dl). Correlation analysis of logarithmic value of uNGAL with logarithmic value urinary protein creatinine ratio and correlation analysis of logarithmic value ofuNGAL with logarithmic value of estimated GFR were assessed by using Spearman rank correlation test. Results:Among 51 children, 38 were in relapse and 13 were in remission. Urinary NGAL demonstated a significant (p<0.001) positive correlation with spot urine protein creatinine ratio. There was no significant correlation between urinary NGAL levels and GFR. Conclusion:Urinary NGAL level significantly correlated with INS relapse but not with glomerular filtration rate. JAFMC Bangladesh. Vol 15, No 2 (December) 2019: 144-147